Five Amino Acid Substitutions in the S1 Unit of Infectious Bronchitis Virus Are Critical Determinants Enhancing Its Adaptation to Vero Cells - Zhichao Cai; Mingjing Zhang; Shouguo Fang (Veterinary Sciences)
The S1 subunit of the spike protein of avian infectious bronchitis virus (IBV) plays a crucial role in determining its host range and cell and tissue tropism. Following the continuous passage of IBV-EP3 through Vero cells over up to 65 generations, a total of 19 amino acid mutations accumulated in the S1 region of IBV-P65. To investigate the impact of these mutations on the adaptability of IBV to Vero cells, six recombinant viruses carrying either a subset or all of the identified mutations were constructed and obtained via a reverse genetics system. Analyses on the growth characteristics of these recombinant viruses and Western blot detection of the expression levels of their spike proteins indicated that the IBV mutant obtained by replacing the amino acid sequence from positions 179 to 323 in the S1 region of IBV-P65 with the corresponding segment from IBV-EP3 S1 significantly impaired viral growth and exhibited a lower replication efficiency in Vero cells, suggesting that five amino acid substitutions (T181I, I246T, F267C, T273I, Q296K) within this region could enhance the adaptation of IBV to Vero cells.